Deformation and Failure Process of Slope Caused by Underground Mining: A Case Study of Pusa Collapse in Nayong County, Guizhou Province, China - Shaozhen Xiong; Wenbing Shi; Yong Wang; Chun Zhu; Xiaoxiao Yu (Geofluids)
Pusa village is located in the karst mountain area of Nayong County, Guizhou Province, China. Laoyingyan mountain rock is gently dipping, the upper part consists of hard rock formations, and the lower part is made up of soft rock composed of 3 coal seams. On August 28, 2017, a massive landslide occurred in this area, resulting in 82,3000 m3 of debris, which resulted in significant casualties and brought up the malaise in society. In this paper, the geological conditions and long-term mining activities in the study area are analyzed by field investigation. The base friction tests and numerical models are used to simulate and analyze the failure and deformation process of Pusa collapse to accommodate the research on the deformation and failure mechanism of the slope and provide better prevention and treatment suggestions. The results show that the Pusa collapse can mainly be attributed to unique geological conditions, underground mining activities, and the topography of the slope. The intensified mining activities promoted the development of fractures and cracks in the slope, resulting in unstable upper slopes. The failure process of the Pusa collapse can be summarized into four-stage: the development of goaves roof deformation, the crest of the slope cracks, intensification of deformation, and occurrence of collapse. The upper slope with high strength rock developed crack-toppling failure. Meanwhile, the upper slope with low strength rock developed subside-crack-sliding failure, and those two failures together contributed to the mechanism of Pusa collapse. Slope deformation and failure mechanism can be summarized as subside-crack-toppling-shear sliding type.